Alternative fuels in shipping: Discussion on the findings of two recently published, independent bibliometric studies. (1st March 2022) - Kołakowski, Paweł; Ampah, Jeffrey Dankwa; Wróbel, Krzysztof; Yusuf, Abdulfatah Abdu; Gil, Mateusz; Afrane, Sandylove; Jin, Chao; Liu, Haifeng
Abstract: A recent publication of two independently performed studies investigating a very similar topic of green shipping, applying very similar methods (bibliometric analysis) on very similar data sets (scientific databases) provides an opportunity for an unbiased analysis of what factors can impact the outcome of one's research. This discussion paper reviews and compares the two following papers: Ampah, J.D., Yusuf, A.A., Afrane, S., Jin, C., Liu, H., 2021. Reviewing two decades of cleaner alternative marine fuels: Towards IMO's decarbonization of the maritime transport sector. J. Clean. Prod. 320, 128871. https://doi.org/10.1016/j.jclepro.2021.128871 Kołakowski, P., Gil, M., Wróbel, K., Ho, Y., 2021. State of play in technology and legal framework of alternative marine fuels and renewable energy systems: a bibliometric analysis. Marit. Policy Manag. https://doi.org/10.1080/03088839.2021.1969460 This paper aims to conclude on the insights arising from both papers concerning their different methodological peculiarities. Highlights: Commentary on two independent bibliometric studies on alternative fuels for shipping. Similarities and differences of both studies discussed. Current commentary offers key insights into the use of bibliometric analysis.